Awareness And Knowledge Of Glaucoma Among Workers In A Primary Public Health Centre In Rote Ndao - Tefbana, Setya Ningrum; Haning, Joy Aprianis (Universitas Nusa Cendana, 2021)
Glaucoma was one of the biggest causes of blindness in the world. Early detection of glaucoma is important to reduce the morbidity of visual impairments and blindness. Primary Public Health Centre is expected to be able to educate people about visual impairment and blindness due to glaucoma. This study aims to evaluate the level of awareness and knowledge about glaucoma in the staff of UPTD Puskesmas Delha as a way to increase the public awareness campaigns of glaucoma. Methods An observational study took place in the primary public health centre, UPTD Puskesmas Delha in West Rote District, Rote Ndao Regency, East Nusa Tenggara Province. The population was all staff, divided into two groups that were health workers and non-health workers. The subjects filled a questionnaire about the awareness and knowledge of glaucoma that was consisting of 12 questions. Data collected were analyzed by SPSS software version 21 using the Independent T-Test method with a significance level of 5%. Result A total of 51 staff participated in this study consisting of 7 males (13.7%) and 44 females (86.3%), age distribution between 22-54 years old. A total of 44 health workers (86.3%) and 7 non-health workers (13.7%), 84.3% aware of glaucoma, but only 62.7% has good knowledge. The result of Independent-T test P-value=0.084 (p >0.05). Conclusion there is no significant difference in awareness and knowledge of glaucoma between health workers and non-health workers. Continuing education is needed to improve the awareness and knowledge of glaucoma.